A Novel Synthesis of Rod-shape BaNiSn-Graphene Decorated TiO 2 Composite as a Ternary Photocatalyst to Improve Visible-Light Driven H 2 Evolution with Lactic acid and TEA - Yonrapach Areerob; Md Nazmodduha Rafat; Kefayat Ullah; Won-Chun Oh (My University, 2022)
Abstract A novel rod-shape BaNiSn-Graphene oxide decorated TiO 2 composite (BaNiSn-GT) has beeen synthesized using a simple ultrasonic method to enhance the visible-light-driven H 2 evolution. The unique structure between the interfaces of BaNiSn-Graphene and TiO 2 provides graphene oxide of contact and excellent electron transfer for H 2 evolution activity. The BaNiSn-GT ternary photocatalyst showed that the BaNiSn-GT displayed the highest H 2 -production rate of 1012 µmol h -1 g -1 , which was about 4 times that of rod-shape BaNiSn and BaNiSn-G under visible light irradiation with scavenger media. Moreover, the higher photocurrent density of BaNiSn-GT is correlated with electron-hole recombination, providing evidence for its inhibition, which leads to a longer lifetime of carriers produced by photoelectrons. The mechanism of the photocatalytic H 2 evolution of BaNiSn-GT based on a full physicochemical characterization was proposed. This study provides new insight into the efficient hydrogen-evolution of graphene-based photocatalysts.
Keywords: Photocurrent; Visible spectrum; Photoelectric effect; Advanced Photocatalysis Techniques